Explaining inequalities of homeschooling in Germany during the first COVID-19 lockdown - Sari, Elif; Bittmann, Felix; Homuth, Christoph (Frontiers in Education, 2023)
Current studies suggest that the COVID-19 pandemic is worsening existing social inequities in the field of education worldwide. In this paper, we argue that the pandemic is especially challenging for students from socially disadvantaged and educationally deprived homes, as parental engagement and resources are very important in terms of guiding and supporting students’ learning processes during this school closure period. To examine how well parents were able to help their children with schoolwork during the homeschooling period in Germany, we used data from the German National Educational Panel Study (NEPS) collected during the first such period in May/June 2020. Taking known mechanisms of inequality of educational opportunity into account, we explored the effects of parents’ aspirations and cultural, social, and economic capital on their ability to help their children. Our results showed that although the majority of the examined parents were able to provide good schoolwork support, as expected, we found inequalities related to social background. Parents with low education were twice as likely as highly educated parents to be unable to provide sufficient support. In our multivariate analyses, family resources had a significant positive effect on the likelihood of a parent being able to help. Moreover, regardless of the social or cultural capital endowment of the parents, good household technical equipment was associated with a higher probability of support. Thus, ensuring that students have access to technical home equipment could be a way to promote an educationally supportive learning environment across all social groups.